Toxicidade de extratos vegetais ao percevejo bronzeado do eucalipto Thaumastocoris peregrinus (hemiptera: heteroptera: thaumastocoridae) e organismos não-alvo - Haas, Jucelaine (2015)
Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae ) is an insect from Australia which is causing severe damage to eucalyptus crops around the world. When feeding from the leaves sap, it causes bronzening, and in extreme cases, may lead to the tree death. Control methods have been studied and the most promising so far is the egg parasitoid Cleruchoides noackae (Hymenoptera: Mymaridae). Alternative products from plants with insecticidal properties could also be a viable option, and they might even be used concomitantly with C. noackae, aiming for a most effective control, but still safe for the environment. Thus, the objective of this work was to verify the action of 5% aqueous plant extracts of Matricaria chamomilla, Echinodorus grandiflorus, Punica granatum, Maytenus ilicifolia a n d Origanum majorana on T. peregrinus. In addition, we aimed to study the extracts potential toxicity to C. noackae and Gallus domesticus L., since the plant compounds might have negative effect upon the non-target organisms. At first, HPLC (High Performance Liquid Chromatography) was used to verify which phenolic compounds would be found in the plant extracts. These were tested on bronze bug adults, in confinement test (to verify the insecticidal action of the extracts) and free-choice test (to verify the repellency). The extracts that showed better results were selected for further tests with non-target organisms. Regarding C. noackae, pre-parasitism and post-parasitism, confinement and free-choice tests were performed to verify if the extracts would affect the host-choosing by the female or the development of the immature stages of the parasitoid. To verify if the extracts would be toxic to G. domesticus, the plant extracts were added to young birds feed for five days. Parameters such as weight gain, food intake, quantification of serum enzymes and histopathological analysis were carried out. HPLC analysis detected gallic, ferulic, vanillic, caffeic and cumaric acid in the extracts samples. All plant extracts tested reduced T. peregrinus survival, but E. grandiflorus, Matricaria chamomilla Maytenus ilicifolia had also a repellent effect, and were tested on the non-target organisms. None of these extracts affected neither the host choice by C. noackae nor adult emergency, when compared to the control group. In addition, the extracts did not cause alterations in any of the studied parameters. Thus, we verified that E. grandiflorus, Matricaria chamomilla and Maytenus ilicifolia have potential to be used to control T. peregrinus and are safe to C. noackae and G. domesticus.